Family relationships and familial responses to health issues (Contemporary perspectives in family research)
In good and bad times? The influence of current relations with extended kin on negative life events / Martijn J.A. Hogerbrugge, Aafke E. Komter -- "No relationships, no emotions, just sex" : exploring undergraduates' sexual decision making in friends with benefits relationships / Christina L. Scott, Belinda Carrillo, Irma M. Rivera -- Multiple sclerosis and parenting : how our children respond to diagnosis, treatment, and daily life / Darbi J. Haynes-Lawrence, Adam R. West -- Extramarital relationships in the context of spousal Alzheimers' disease : a mixed-methods exploration of public attitudes / Andrew S. London, Janet M. Wilmoth -- Work-family conflict and depression for employed husbands and wives in Japan : moderating roles of self and spousal role involvement / Tetsushi Fujimoto, Sayaka K. Shinohara, Tsuyoshi Oohira -- Single mothers with breast cancer : relationships with their children / Amanda C. Ginter, Bonnie Braun -- Parental caregiving for a child with special needs, marital strain, and physical health : evidence from national survey of midlife in the U.S. 2005 / SunWoo Kang, Nadine F. Marks -- Mothers' perceptions of family communication patterns when having an ADHD child / Anita Hoag -- Families of children with autism spectrum disorder : the role of family-centered care in perceived family challenges / Jennifer S. Reinke, Catherine A. Solheim -- Multiple segment factorial vignettes in family health interventions / Marilyn J. Coleman, Lawrence H. Ganong, Jacquelyn J. Benson -- Black-white differences in formal ADHD diagnosis : unmet need, or conscious decision-making process? / Jessica Streeter